PENGHAMPIRAN ”NEO FUZZY NEURON” WACANA DALAM RANCANGAN KONSEPSUAL SISTEM PENILAIAN KARYAWAN - Budisantoso Wirjodirdjo (EKUITAS (Jurnal Ekonomi dan Keuangan), 2008)
Computation and information technology progress in the last three decades gives real impact for management practice development. Currently some uncertainties in receiving information on management policy response is easier to be predicted. in terms of staff evaluation, inaccuracy of staff performance evaluation due to lack of good instrument caused low guarantee of objective evaluation result  and free of un-bias evaluator. Neo Fuzzy Neuron approach is a thinking method which orient to human intellectual concept and to computation and information technology. This offer an alternative to predict staff behaviour evaluation. As a thinker concept, this approach can be ued as a base in developing a decision to support system in evaluating staff performance objectively and accurately; and has quite good operational feasibility.